Degradation Of Methylene Blue Using Cuo Prepared Using Conventional Solid State Method - Tai, Ming Li (Universiti Sains Malaysia, 2017)
The degradation of methylene blue (MB) dye onto copper oxide (CuO) synthesized using solid state method was investigated in a batch adsorption process. Copper Oxide (CuO) was successfully synthesized using solid state synthesis which involves heat treatment with temperatures from 400oC to 600oC. The optimum preparation temperature was 600oC, which have resulted in 8.5% MB removal. XRD analysis shows that the crystal system of CuO is a monoclinic system and therefore all the diffraction peaks has been indexed using the CuO monoclinic phase. The obtained parameters were a = 4.6860Å, b = 3.4280Å, c = 5.1330Å with a volume cell of 81.84 Å3. SEM analysis indicates that a standard particle size for CuO is 37.0μm and that it has irregular surface. The effect of initial dye concentration (100ppm-600ppm), contact time (24-48 hours) and solution temperature (30⁰C) were also evaluated through. Highest percentage of removal of MB was observed in MB concentration of 600ppm. A longer contact time of 48 hours was shown to be more effective than 24 hours. As a conclusion, the adsorption of MB onto CuO has higher efficiency at larger concentration difference, longer contact time and higher temperature used for CuO synthesis.